Genotype x environment interaction and pre‑weaning traits in Simmental animals in two birth seasons - Solar Diaz, Iara Del Pilar; de Araujo Neto, Francisco Ribeiro; Marques, Luis Fernando Aarão; de Oliveira, Henrique Nunes (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to evaluate the effect of the genotype x environment (GxE) interaction on weaning weight and weight gain from birth to weaning, in Simmental males and females born in the rainy and dry seasons. Twenty thousand animals were evaluated at 210 days of age. A multitrait analysis was performed, in which the same feature was considered distinct for the different environmental groups; and a single trait analysis was done, in which each trait was considered as the same in all environmental groups. The GxE interaction was assessed by genetic correlation (rg). The interactions were considered important when rg values were below 0.80. The posterior distributions of heritability estimates showed the absence of heterogeneity of the variances between sexes, although there was GxE interaction between the environmental groups. The observed values of genetic correlation were 0.54 to 0.78 and 0.55 to 0.75 for weight at weaning and weight gain from birth to weaning, respectively. The selection based both on the single trait and on the multitrait analysis showed no significant differences for genetic gain of the animals. Birth seasons have effect on the evaluated traits in all environmental groups, and the GxE interaction is more evident in females than males.